Post-queer politics - Ruffolo, David (Ashgate, 2009)
In Post-Queer Politics, Ruffolo looks at the work of Foucault, Butler, Bakhtin, Deleuze, Guattari and others in his creative refocus on the queer/heteronormative dyad that has largely consumed queer studies and contemporary politics. His radical and intersectional new way of thinking will appeal to readers across a range of subjects, including gender and sexuality studies, philosophy, cultural studies, political science and education.
Keywords: approches et analyses; cours; discipline; histoire et politique; hétéronormativité; hétérosexisme; intersectionnalité; lit4700; philosophie; premier cycle; queer; ressource en ligne; science politique; science politique et droit; sciences de l'éducation; sciences humaines; sofia; systèmes d'oppressions; thématiques